Die Kirche und die "Kärntner Seele" - Thonhauser, Johannes (2020)
This study deals with the percepetion of the Catholic church in Carinthia, a federal state of Austria, especially during the austrofascist era from 1933/34 to 1938. Therefore, important historical stages in Carinthian history are outlined and so far unpublished archive material is analyzed. After all, particular facets of the Carinthian habitus are illustrated by text and image samples from arts, literature, and historiography